Development and implementation of a nurse-led walk-in centre: evidence lost in translation?. (July 2013) - Desborough, Jane; Parker, Rhian; Forrest, Laura
Objectives: The design of the first Australian public nurse-led primary care walk-in centre was modelled on those established in the English National Health Service (NHS). An independent evaluation of the first 12 months of operation of the Australian Capital Territory (ACT) Health walk-in centre, in 2011, analysed the translation of evidence from the national evaluation of the NHS walk-in centres to the policy development and implementation of the ACT walk-in centre. Whilst in a number of ways the evidence was used well, our interest for this paper was to examine three areas identified as problematic and to identify the points at which the evidence was lost or diluted. Methods: In addition to data obtained through nurse and key stakeholder interviews for the evaluation, an analysis was undertaken of documents on the planning and establishment of the ACT walk-in centre, either provided to the evaluation team or made publicly available. Results: Three areas were identified as problematic in the way that evidence from the NHS evaluation was translated: the use of clinical decision support software (CDSS); the marketing of the walk-in centre; and its location. Conclusions: Our examination indicates that despite seeking evidence to inform the development of the ACT walk-in centre, the evidence was not fully used and some clear lessons ignored, resulting in much of the evidence being lost in translation.